Direct formation of Al2O3/GdAlO3/ZrO2 ternary eutectic ceramics by selective laser melting: Microstructure evolutions. Issue 15 (December 2018) - Liu, Haifang; Su, Haijun; Shen, Zhonglin; Wang, Enyuan; Zhao, Di; Guo, Min; Zhang, Jun; Liu, Lin; Fu, Hengzhi
Abstract: Highly dense Al2 O3 /GdAlO3 /ZrO2 ternary eutectic ceramics are firstly formed by a novel one-step selective laser melting method directly from mixed ceramic powders without post-sintering treatment. The evolutions of microstructure and micro-mechanical properties in a single track solidification are investigated. The as-built eutectic ceramics consists of only Al2 O3, GdAlO3 and ZrO2 phases with uniform three-dimensional network structure in the sub-micron size. Three continuous transitions from "Chinese script" structure to rod-like eutectic, "Chinese script" structure to lamellar eutectic, and lamellar to rod-like eutectic are found in the single melted pool due to the variations of the eutectic growth behavior and volume fraction of the constituent phases. The interphase spacing decreases from 0.92 μm to 0.48 μm with increasing the solidification rate, and the relationship between them satisfies λ = 4.82 × V s − 1 2 . The hardness slightly increases from 14.3 to 15.3 GPa, and the fracture toughness increases from 6.1 to 7.8 MPa m 1/2 from the surface to bottom of the molten pool. The property differences in the molten pool can be primarily attributed to that cracks propagate in a straight line in the top zone, while the crack bridging and arrest are formed in the GAP phase in the bottom zone.